A implicação da família na gestão de empresas familiares - Amaral, Ana Patricia de Souza (2015)
In the family business the existence of family conflicts, added to the competitiveness and innovation in the business market requires a look at new strategies needed, the role of management in the conduct of proceedings, and the reflection of the attitudes of it in other people who make family businesses. This study aimed to observe the family implications for the incidence of present conflicts in family businesses, from the perspective of managers. Specifically craved: to identify the main types of conflicts experienced by managers and its consequences in the company; understand the strategies used by managers to deal with conflicts arising from his family in the workplace; list the most frequent situations generate conflicts. Three men and a woman, managers of family businesses, in the age group 57-73 years, participated in the qualitative survey. All are married, have children and have education between high school and / or university, founders of companies located in the city of Recife. In addition to a sociodemographic questionnaire, we used a semi directed interview, made up of four issues that meet the research objectives, as well as a photo album with eleven figures, addressing issues related to work and family. The analysis of the interviews and responses to the figures was made from the Content Analysis. In general, the results show that the three companies are consolidated in the market. About the existence of conflicts were identified: differing views among family members, making tough decisions that can affect or hurt family, lack of career path that can lead to inequality. With regard to the strategies used by managers to deal with conflicts, they were listed: dialogue, have left field, knowing retreat when the other has reason, impartiality in decisions. As for the situations that generate more conflicts were mentioned: delays or defaults by family members who do not invest in the company, arrival of new members in the family and no distinction between the family and the workplace. Future research is needed to develop further on the subject.